Mr. Colostomy - Thurber, Matthew (Drawn & Quarterly, 2022)
"Who is Mr. Colostomy? Why, he's a manifestation of a searching consciousness, a marginally employable horse detective who sleeps outside, standing up. He opens up cans of worms faster than they can restock the Goya on your bodega shelves. Thurber's daily strip honors the mistake as the desired or hidden expression of the unconscious. All that matters is that the comic is funny, or real, or neither!"--